PENYULUHAN PENTINGNYA MENGENALKAN DAN MEMPERAKTEKKAN TATACARA BERWUDHU YANG BENAR PADA SISWA-SISWI TK PWP II PERTAMINA PLAJU (JURNAL PENGABDIAN KEPADA MASYARAKAT (ABDIMAS) UNIVERSITAS BATURAJA, 2022)
Thaharah according to language means clean and holy, according to the term (fiqj experts) it means to clean oneself from hadast or unclean things such as bathing, ablution and tayamum. While ablution is one of the purification of small hadast before praying. The wahib ablution command did come down at the same time as the obligatory prayer command, approximately one year and a half before the hijri year (Q.S Almaidah verse 6). And the Messenger of Allah said, "Indeed, a person's prayer will not be complete until he completes his ablution and as Allah has taught him to wash his face, hands up to the elbows, wipe his head and wash his feet to the ankles" (HR Ibn Majah from Rifa'ah bin Rofiah ra. ) While the water used for ablution is mutlaq water, which is holy again purifying water. Therefore, in this service, we try to introduce students, especially TK PWP II Pertamina Plaju students so that they can know and practice the correct ablution procedures and be able to apply them in daily life. Meanwhile, to make it easier for TK PWP II Pertamina Plaju students, we deliver material by playing a CD cassette about the correct ablution procedure.